Seasonal wind analysis in Limassol, Cyprus, using the ground-based Doppler LiDAR of the CARO National Facility - Chrysostomou, Konstantinos; Kotsias, George; Seifert, Patric; Nisantzi, Argyro; Hadjimitsis, Diofantos G.; Mamouri, Rodanthi-Elisavet (My University, 2025)
The study focused on utilizing, for the first time ever, the data of the Halo Photonics Streamline XR Doppler LiDAR (Snoopy), which is an active remote sensing instrument that since January 2023 has been operating at the National Facility of the Cyprus Atmospheric Remote-Sensing Observatory (CARO) located in Limassol, Cyprus. The data spanned two full years of observations, from February 2023 to January 2025, in order to analyze the average wind patterns over the city, with the aim of understanding the diurnal, as well as the monthly and seasonal variations in both the horizontal wind speed and direction. The research involved processing data collected at various times of the day and across different atmospheric heights to calculate the mean horizontal wind and to identify common or characteristic patterns in the behaviour of the wind across months or seasons. An important outcome of this procedure is that the behaviour of the wind of this region can be sufficiently described through its separation into two periods of six months: the warm one from May till October, and the cold one from November until the month of April. The study also highlights the influence that local topographical factors have on the observed wind patterns, as both the land and sea breezes present a diurnal cycle and constitute a key characteristic of the winds that affect the city.